2003
DOI: 10.1128/aac.47.12.3784-3788.2003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Unformulated and FormulatedDendrimer-Based Microbicide Candidates in Mouse and Guinea PigModels of GenitalHerpes

Abstract: Prevention of sexually transmitted infections is a priority in developed and developing countries. One approach to prevention is the use of topical microbicides, and one promising approach is the use of dendrimers, highly branched macromolecules synthesized from a polyfunctional core. Three new dendrimer products developed to provide stable and cost-efficient microbicides were initially evaluated in vitro for anti-herpes simplex virus activity and then in vivo by using a mouse model of genital herpes. From the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
102
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 19 publications
7
102
0
2
Order By: Relevance
“…Among these, dendrimers and dendrimer-like molecules have recently been generated with surfaces formed of negative charges and screened for potential anti-herpes activities. Indeed, in vitro analysis has revealed that sulfonated and carboxylated polylysine dendrimers effectively block the HSV-1 and -2 infection of cells and non-primate animal studies have shown that they were able to protect animals against an intravaginal HSV-2 challenge (Bourne et al, 2000;Bernstein et al, 2003;Gong et al, 2005). However, in addition to inhibiting the HSV attachment, the sulfonate ddendrimers were also shown to act at a post-entry level by apparently inhibiting HSV DNA synthesis, which suggests that they could be used not only for prevention of HSV infection but also as inhibitors of viral replication (Gong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, dendrimers and dendrimer-like molecules have recently been generated with surfaces formed of negative charges and screened for potential anti-herpes activities. Indeed, in vitro analysis has revealed that sulfonated and carboxylated polylysine dendrimers effectively block the HSV-1 and -2 infection of cells and non-primate animal studies have shown that they were able to protect animals against an intravaginal HSV-2 challenge (Bourne et al, 2000;Bernstein et al, 2003;Gong et al, 2005). However, in addition to inhibiting the HSV attachment, the sulfonate ddendrimers were also shown to act at a post-entry level by apparently inhibiting HSV DNA synthesis, which suggests that they could be used not only for prevention of HSV infection but also as inhibitors of viral replication (Gong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Unmodified polycationic PAMAM dendrimer showed greater affinity towards TAR-RNA than viral Tat protein. [70] Bernstein and colleagues [67] also reported that the outer sulfonic acid surface of lysine-based dendrimers attaches through thiourea (SPL2999) or amide (SPL7013, SPL7015 and SPL7032) linkages (Figures 4a and b). They evaluated these compounds in vivo in mouse and guinea-pig models of HSV-2-induced genital herpes infection.…”
Section: Prevention Of Virus Binding To the Target Cell Surfacementioning
confidence: 96%
“…[66] Bernstein and colleagues have also investigated the potential of sulfonated polylysine dendrimer with a benhydrylamine core in vivo in mice and guinea-pigs and found that they protected against intravaginal challenge with HSV. [67] Sulfonated dendrimer also protected female pigtail macaques against intravaginal infection with SIV/HIV chimera virus. [31] Similar results were obtained by Bourne and colleagues upon administration of sulfonated (BRI-2999) and carboxylated (BRI-6741) dendrimers (Figure 3d) to mice prior to exposure to HSV.…”
Section: Prevention Of Virus Binding To the Target Cell Surfacementioning
confidence: 98%
“…When administered in mouse vaginas, it rendered a dose-related protection from HSV-2 infection. 46 In macaque monkeys, SPL7013 gels administered in a single intravaginal application was found to be safe and protected macaques against vaginal simian HIV infection.…”
Section: Therapeutic Applications Antibacterial Agentsmentioning
confidence: 99%